SISTEM FONOLOGI DIALEK MELAYU BRUNEI - NURUL ERASHAFIERA SHAMIMI, SAMRA (Universiti Malaysia Sarawak (UNIMAS), 2020)
Brunei Malay dialect ia a minority language spoken by people of Brunei Malay in Brunei Darussalam, Limbang, Lawas, Sipitang and Beufort. This study was conducted with aim of studying the phonological system in Brunei Malay dialect that spoken in Lawas, Sarawak. The objective of this study is to identify the vowel phonemes, consonant phonemes, diphthongs, double vowels and double consonants Brunei Malay dialect in Lawas, Limbang Sarawak. To achieve the objectives, researcher used Asmah’s Descriptive Models (2006) and phonetic theory (Paitoon M. Chaiyanara, 2006). According to the data, there are three vowel phonemes / i, a, u / and 19 consonant phonemes / p, b, t, d, k, ɡ, ʔ, m, n, ɲ, ɲ, ʧ, ʤ, s, h, l , r, w, y / in Brunei Malay dialect. The data also shows that diphthong in Brunei Malay dialect is [ay], [aw] and [uy]. Vowel clusters consist of six types which [it]. [iu], [ai], [au], [ui] and [ua]. Consonant clusters in Brunei Malay dialect is mp, mb, nd, nt, nʧ, nʤ, ŋs, ŋɡ, ŋk sk, kl, rp dan sb.